ASSESSMENT OF SOIL EROSION RISK USING RUSLE IN SELECTED WATERSHEDS OF SULAIMANI PROVINCE, IRAQ - Abdula, Star; Asadi, Hossein; Barzinji, Khalid; Samani, Ali Akbar (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was aimed to assess the risk of soil erosion in 32 watersheds of Sulaimani province, Kurdistan/Iraq, based on Revised Universal Soil Loss Equation, GIS and RS data. The annual precipitation data were used to generate the rainfall-runoff erosivity factor using the previously developed equation for the region. The soil erodibility factor was estimated using soil particle size distribution data. The topographic factor was generated using a digital elevation model from a sentinel 2. The cover-management factor was determined by using Google Earth Engine with Landsat7 and Landsat8. While the soil erodibility and vegetation factors did not show high spatial variability across the province, rainfall erosivity showed an increasing trend from south  west to north east of the region, ranged from 73 to 632 MJ mm ha-1 h-1. The results showed that the average annual soil loss for the different watersheds ranged from 2.12 to 62.05 t ha-1 y-1. The results also indicated that the main factors governing soil erosion in Sulaimani province are rainfall intensity, rugged topography, steep slopes, and sparse vegetation.